The Case of the Million-Dollar Duck: A Hunter, His Treaty, and the Bending of the Settler Contract. Issue 1 (4th February 2019) - Johnson, Miranda
Abstract: In settler states such as Canada, indigenous peoples' claims for sovereignty in the late twentieth century became matters of intense public and political debate. Provoked by widespread indigenous rights activism of the 1970s, the Canadian state embarked on a large-scale examination of claims for rights and restitution. By focusing on the 1962 case of a duck hunter who insisted on his treaty right to hunt as he pleased in a Canadian borderlands region that was becoming more tightly woven into the fabric of the settler nation, this article argues for the value of recovering the discursive strategies of indigenous peoples in making sovereign claims prior to 1970s activism. I suggest that such claims were effective in bending the "settler contract, " which refers to the founding of settler states in dispossession and the silencing of indigenous actors. My approach brings to the fore a distinctive form of non-elite politics, what I call "treaty talk, " or the vernacular stories, civic rituals, and political disputes concerning the treaty promises that Canadian authorities made to northern indigenous communities earlier in the twentieth century. Although treaty talk did not break the settler contract, it posed a significant challenge to settler law and led one judge to reinvent a Canadian myth of benevolent empire.